1996
DOI: 10.1080/10407789608913856
|View full text |Cite
|
Sign up to set email alerts
|

Time-Dependent Interaction Between Water at Supercritical Pressures and a Hot Surface

Abstract: This article presents a numerical study of the thermal and j1uiJIflow interaction driven by the sudden coniaa between satunued liquiJI water (373 J() and a hot (2300 J() spherical or plane surface. It is shown t1wJ under these conditions the sudden contaa is charoderized iniJilUly by single-phase interj'aciDJ waler and supercriJical pressure tiuu decays in time as the water is accelerated away from the interface. The sudden co_ generates (high) temperature, pressure, and density waves ttuupropagate away from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
(47 reference statements)
0
1
0
Order By: Relevance
“…Although steam cannot be strictly modeled as an ideal gas, Craciunescu et al [20] have demonstrated that ideal gas relations can be applied for modeling the interaction of even liquid water at supercritical pressures with reasonable accuracy. Assuming the vapour film to behave as an ideal gas, Eq.…”
Section: Variable Density Modelmentioning
confidence: 99%
“…Although steam cannot be strictly modeled as an ideal gas, Craciunescu et al [20] have demonstrated that ideal gas relations can be applied for modeling the interaction of even liquid water at supercritical pressures with reasonable accuracy. Assuming the vapour film to behave as an ideal gas, Eq.…”
Section: Variable Density Modelmentioning
confidence: 99%